1999
DOI: 10.1177/088572889902200206
|View full text |Cite
|
Sign up to set email alerts
|

Video-based Simulations: Considerations for Teaching Students with Developmental Disabilities

Abstract: Abstract. The use of video-based multimedia simulations for teaching functional skills to persons with developmental disabilities remains an unexplored application of technology for this group. This article examines the historical literature in this area, and discusses future considerations, design issues, and implications of using multimedia simulations. Implementation issues are presented, and suggestions regarding design, development, and application of multimedia simulations are offered. Considerations add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…Some researchers, however, have recommended a combined package of instruction using both simulated and community-based instruction (Bates et al, 2001). This investigation supports the findings of Alcantara (1994), Norman et al (2001), and Mechling et al (2002), who found video recordings to be a viable means to simulate community environments when instruction cannot occur solely through community-based instruction (Wissick et al, 1999). This step was difficult to simulate with the CBI program and required a range of motor responses in actual stores.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Some researchers, however, have recommended a combined package of instruction using both simulated and community-based instruction (Bates et al, 2001). This investigation supports the findings of Alcantara (1994), Norman et al (2001), and Mechling et al (2002), who found video recordings to be a viable means to simulate community environments when instruction cannot occur solely through community-based instruction (Wissick et al, 1999). This step was difficult to simulate with the CBI program and required a range of motor responses in actual stores.…”
Section: Discussionsupporting
confidence: 74%
“…Further, research recommends that simulations closely replicate the relevant stimuli and response variations found in the actual community (Snell, 2000). The use of multimedia, incorporating video recordings, is a form of simulation obtaining increased attention in teaching skills to students with disabilities (Mechling & Gast, 2003;Mechling et al, 2002;Wissick, Gardner, & Langone, 1999;Wissick, Lloyd, & Kinzie, 1992). Video recordings allow realistic replications of the student's environment, and a multimedia approach creates an interactive environment in which the student actively responds to stimuli presented through the computer.…”
mentioning
confidence: 99%
“…Even though researchers have indicated that these methods are effective in teaching grocery purchasing skills to students with ID, they have also reported several potential barriers to using these interventions: (a) constraints of resources such as funds, time, and staff (Mechling & Gast, 2003;Wissick, Gardner, & Langone, 1999;Wissick et al, 1992); (b) insufficient similarity to real world situations (Ayres & Langone, 2002;Hutcherson et al, 2004;Mechling, 2004;Stokes & Baer, 1977); and (c) cumbersome technology (e.g., awkward and time-consuming manual control of DVD/VCR players) (Mechling, 2004) .…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Even though a range of studies on community-based instruction have validated that this intervention is effective and efficient, some issues remain to be addressed in order for practitioners to use it practically (e.g., funds, staff, and time, as well as safety concerns) (Mechling & Gast, 2003;Wissick et al, 1999). Researchers have also suggested that more studies are needed to examine the effectiveness of combinations of community-based instruction and various classroom simulations (Bates et al, 2001).…”
Section: Community-based Instructionmentioning
confidence: 99%
See 1 more Smart Citation